Antibiotic susceptibility pattern of group B streptococcal isolates from maternal genital tract - Sharmila, Vijayan; Babu, Thirunavukkarasu Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Group B streptococcus (GBS) is one of the important cause of early onset neonatal sepsis in developed countries leading to increased neonatal morbidity and mortality. Penicillin and Ampicillin are the drugs of choice for prevention of GBS infections. Antibiotic resistance amongst GBS isolates is an emerging health problem affecting neonates. Hence, this study was performed to determine the antibiotic susceptibility pattern of Group B Streptococcus (GBS) in a population of pregnant women. Methods: A prospective study was done to screen pregnant women for vaginal and rectal GBS colonization during their regular visits to antenatal clinic. Todd-Hewitt broth, an enrichment medium for GBS was used for isolation. The antibiotic susceptibility pattern of the isolates were studied. Results: A total of 300 pregnant women were screened for GBS colonization. GBS colonization rate in our study was 2.3%. The antibiotic susceptibility pattern of the isolates revealed that none of the isolates were resistant to penicillin or clindamycin, while resistance was noted to erythromycin (14.3%) and tetracycline (71.4%). Conclusions: GBS continues to remain sensitive to Penicillin which is the drug of choice for prevention and treatment of GBS. Consistent surveillance of antibiotic sensitivity pattern of GBS as well as for other organisms implicated in new born sepsis and maternal infections is required to formulate guidelines for prevention and treatment.